PENGARUH INDEPENDENSI, KOMPETENSI, DAN TEKANAN WAKTU TERHADAP KUALITAS AUDIT - Irawan Jati Kusumo; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2019)
The purpose of this study is to analyze the relationship between the quality of auditing results with an auditor's independence, the time pressure given, and the auditor's competence. This study uses measures of independence, competence, and time pressure as the dependent variable. This research was conducted by using questionnaire method that was spread to 15 Public Accounting Firms (PAF) with target of eight auditors in each PAF.The results show that independence, competence, and time pressure play a significant role in the quality of audit results.